The use of the cutaneous saphenous nerve as a source of nerve graft material in the dog (the use of the CSN as a graft) - Moissonnier, P.; Vigneron, O.; Duchossoy, Y. (Veterinary and Comparative Orthopaedics and Traumatology, 2001)
This paper analyses the feasibility of using the cutaneous saphenous nerve (CSN) as a source of peripheral nerve graft (PNG). In 34 fresh dog cadavers, the PNG length (PNGL) was measured, pattern of collateralization was studied, fascicles diameter and number were assessed at multiple levels along the length of the CSN (levels of section A, B, C and D) and surgical approach was described. The PNGL was correlated to femoral length. The pattern of CSN collateralization was consistent for all but 2 of the dogs. The average cross section diameter and fascicle number of the CSN was 2.0 to 0.1 mm (1 to 7 fascicles). CSN provides a large-sized, easily accessible nerve graft that could be used to bridge nerve gaps in the dog.
Keywords: Nerve graft; saphenous nerve; dog